A Study of Connectionism Theory - Shahryar Banan; Muhammad Ridwan; Abdurahman Adisaputera (Budapest International Research and Critics University, 2020)
The development of connectionism represents a paradigm shift in science. Connectionism has its root in cognitive and computational neuroscience. Likening the brain to a computer, connectionism tries to describe human mental abilities in terms of artificial neural networks. A neural network consists of a large number of nodes and units which are joined together to form an interconnection network. Within these interconnections, knowledge is distributed. Therefore learning is a processing by-product. This article is about the concept of connectionism, what it accounts for and what it doesn't take into account. Finally, different approaches to connectionism are discussed.